1997
DOI: 10.1017/s0022112097004916
|View full text |Cite
|
Sign up to set email alerts
|

Added stresses because of the presence of FENE-P bead–spring chains in a random velocity field

Abstract: FENE-P bead-spring chains unravel in the presence of large enough velocity gradients. In a turbulent flow, this can result in intermittent added stresses and exchanges of energy between the chains and the fluid, whose magnitudes depend on the degree of unravelling and on the orientations of the bead-spring chains. These effects are studied by calculating the average behaviour at different times of an ensemble of chains, contained in a fluid particle that is moving around in a random velocity field obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Although we can only simulate MDR using a minimal channel flow, the fact that (i) turbulence is sustained in the reference case and (ii) f x = 0 leads to relaminarization indicates that the turbulence enhancing activity in the streamwise direction that we have isolated is the key of the selfsustained generation process of turbulence at MDR. This point was also inferred by [22] by using FENE-P bead-spring chain in turbulent flow.…”
Section: Numerical Experimentsmentioning
confidence: 53%
See 1 more Smart Citation
“…Although we can only simulate MDR using a minimal channel flow, the fact that (i) turbulence is sustained in the reference case and (ii) f x = 0 leads to relaminarization indicates that the turbulence enhancing activity in the streamwise direction that we have isolated is the key of the selfsustained generation process of turbulence at MDR. This point was also inferred by [22] by using FENE-P bead-spring chain in turbulent flow.…”
Section: Numerical Experimentsmentioning
confidence: 53%
“…By investigating the polymer body force, it is established that polymers reduce turbulence by opposing the downwash and upwash flows generated by near-wall vortices, while they enhance streamwise velocity fluctuations in the very near-wall region. The numerical experiments allow us to characterize the importance of each component of the polymer body force on the drag-reducing and turbulence-enhancing properties found or suggested in other publications [7,22,27]. The exact localization of polymer drag-reducing activity is now crucial for the development of a predictive model for polymer drag reduction.…”
Section: Resultsmentioning
confidence: 91%
“…Later work by the same group found that the stresses introduced by the stretched polymers in a turbulent flow lead to added dissipations, both positive and negative. 36 The positive dissipations are associated with the streamwise vortices in the near-wall region and would decrease the production of Reynolds shear stress in these structures. A study of FENE dumbbells in steady, Gaussian ran- dom flows shows that stochastic flow fields can produce large conformation changes in the polymer.…”
Section: Polymers In Lagrangian Time-dependent Flowsmentioning
confidence: 99%
“…By comparing the performance of the various polymer models in the same flow field, we obtain a quantitative estimate of the error associated with the FENE-P model. Our approach is similar to the one taken by Zhou and Akhavan (2003) and others (Massah and Hanratty 1997, Massah et al 1993. However, those studies focused on inhomogeneous turbulent channel flow, where the statistics of the trajectory are a strong function of the initial condition.…”
Section: Introductionmentioning
confidence: 98%